POTENSI VITAMIN D SEBAGAI OBAT PREVENTIF UNTUK MENGHAMBAT PROGRESIVITAS TENSION TYPE HEADACHE - Elvan Wiyarta; Stefen Weliadi Ali (PERDOSNI, 2021)
Tension type headache (TTH) is one of the most common primary headaches. The prevalence of this headache is very high in Indonesia. Even so, many people still ignore this disease and eventually come when it has progressed to chronic. Several drugs have been developed to inhibit the progression of TTH, but they have some drawbacks. As an alternative, vitamin D is alleged to be able to act as an inhibiting drug for TTH progression through its mechanism of muscle spasm. The role of vitamin D is mainly found in the system of muscle contractility disorders that occur in TTH. Several clinical studies also support this theory. Vitamin D also has high applicability as a preventive drug for the progression of TTH, in terms of effectiveness, compliance, safety, and cost. Therefore, vitamin D has the potential to act as an inhibiting drug for TTH progression. However, further studies still need to be done. Keyword: , tension type headache, vitamin D